“Beyond being analysts of doom”: scientists on the frontlines of climate action - Artico, Daniele; Durham, Sarah; Horn, Laura; Mezzenzana, Francesca; Morrison, Malik; Norberg, Anna (Frontiers in Sustainability, 2023)
What happens when academics become activists? In this paper, we discuss principles, commitments and experiences of Scientist Rebellion (SR), a movement of scientists, academics, and researchers committed to activism, advocacy and non-violent civil disobedience against the (in)actions of governments, corporations and other institutions, including academic ones. In sharing experiences from the frontlines of direct actions with SR along with the perspectives from individual scientists, coming from a variety of geographical locations, and a range of academic levels and disciplines, we reflect on the need to transgress the boundaries of a system of knowledge production and education that is effectively reproducing the very structures that have led us into climate and ecological crises. This study provides a reflective and critical engagement with Scientist Rebellion, drawing on a range of interviews with activists, as well as material from and about Scientist Rebellion. We conclude with a reflection on the relation between scientists and their institutions, as well as a mobilising plea to the scientific community to take action.